Dieulafoy’s lesion: an unexpected and rare cause of upper gastrointestinal bleeding - Saravana Kumar Rajanthran; Harjit Chaal Singh; Da Jun Than; Firdaus Hayati (BMJ Publishing Group, 2020)
A 51- year- old man with multiple comorbidities of hypertension, chronic kidney disease, dyslip-idaemia and a history of stroke was presented to the emergency department with a 1 day epigastric pain. He was subsequently diagnosed with hyper-tensive emergency and inferior myocardial infarc-tion. Despite being administered an intravenous infusion of glyceryl trinitrate (GTN), his condition deteriorated and he developed cardiac arrest with ventricular fibrillation, which required cardiopul-monary resuscitation and defibrillation. The patient had stormy recoveries with multiple episodes of hospital- acquired pneumonia and prolonged intu-bation due to failed extubation. He was put on double antiplatelet medication and subcutaneous low- molecular weight heparins injection.